(untitled) (Journal of Nobel Medical College, 2019)
Background: Patients with Acute ST-elevation myocardial infarction (STEMI) have different modes of presentation, treatment options and outcomes which vary across the different population. There is a paucity of data about the clinical characteristics of acute STEMI from the eastern part of Nepal. Our study aimed to assess the clinical characteristics and in-hospital outcome of patients with acute STEMI at a tertiary care center of the eastern part of Nepal. Materials and Methods: This is a descriptive cross-sectional study on 214 patients who presented in the emergency room or coronary care unit of Nobel Medical College Teaching Hospital from August 2018 to July 2019. Demographic features, risk factors, duration of symptoms before presentation, different treatment options offered and the in-hospital outcome were noted. Results: The male to female ratio was 2.14. The most common symptom was chest pain (97.0%) followed by sweating 78.0%, breathlessness 29.0%, nausea or vomiting 24.8 %, etc. The most common regional territory involved was the anterior wall (48.1%) followed by the Inferior wall (42.5 %), posterior wall (5.1 %). The majority (71.3%) presented within 12 hours after symptom onset. Hypertension was the most frequent (40.2%) risk factor followed by Smoking (39.7%), diabetes mellitus (35.0%) and dyslipidemia (34.6%). Among patients eligible for primary PCI - 76.6% underwent PCI, 22.0% were managed conservatively. Total mortality among patients managed with primary PCI was 3% as compared to medical therapy (14.8%). Heart failure prevalence was less with primary PCI (12.1%) compared to medical therapy (29.6%). Conclusion: The majority of patients presented with typical symptoms in a reasonably early period (12 hrs) and the in-hospital outcome was better with primary PCI. Hence, efforts should be made to offer primary PCI to the majority of patients in the peripheral part of our country.